CO2 Increase Experiments Using the CESM: Relationship to Climate Sensitivity and Comparison of CESM1 to CESM2 - Bacmeister, Julio; Hannay, Cecile; Medeiros, Brian; Gettelman, Andrew; Neale, Richard; Fredriksen, Hege-Beate; Lipscomb, William H; Simpson, Isla; Bailey, David; Holland, Marika; Lindsay, Keith; Otto-Bliesner, Bette (Journal of Advances in Modeling Earth Systems, 2020)
We examine the response of the Community Earth System Model Versions 1 and 2 (CESM1 and CESM2) to abrupt quadrupling of atmospheric CO2 concentrations (4xCO2) and to 1% annually increasing CO2 concentrations (1%CO2). Different estimates of equilibrium climate sensitivity (ECS) for CESM1 and CESM2 are presented. All estimates show that the sensitivity of CESM2 has increased by 1.5 K or more over that of CESM1. At the same time the transient climate response (TCR) of CESM1 and CESM2 derived from 1%CO2 experiments has not changed significantly—2.1 K in CESM1 and 2.0 K in CESM2. Increased initial forcing as well as stronger shortwave radiation feedbacks are responsible for the increase in ECS seen in CESM2. A decomposition of regional radiation feedbacks and their contribution to global feedbacks shows that the Southern Ocean plays a key role in the overall behavior of 4xCO2 experiments, accounting for about 50% of the total shortwave feedback in both CESM1 and CESM2. The Southern Ocean is also responsible for around half of the increase in shortwave feedback between CESM1 and CESM2, with a comparable contribution arising over tropical ocean. Experiments using a thermodynamic slab-ocean model (SOM) yield estimates of ECS that are in remarkable agreement with those from fully coupled Earth system model (ESM) experiments for the same level of CO2 increase. Finally, we show that the similarity of TCR in CESM1 and CESM2 masks significant regional differences in warming that occur in the 1%CO2 experiments for each model.
Keywords: Sørishavet; atmosfæren; fysikk; karbondioksid; klimaendringer; klimagasser; klimamodeller; klimatologi; menneskelig påvirkning; meteorologi; skyer

Evolution of the Antarctic Ice Sheet Over the Next Three Centuries From an ISMIP6 Model Ensemble - Seroussi, Hélène; Pelle, Tyler; Lipscomb, William H.; Abe-Ouchi, Ayako; Albrecht, Torsten; Alvarez-Solas, Jorge; Asay-Davis, Xylar; Barre, Jean-Baptiste; Berends, Constantijn J.; Bernales, Jorge; Blasco, Javier; Caillet, Justine; et al. (Earth's Future, 2024)
Abstract The Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6) is the primary effort of CMIP6 (Coupled Model Intercomparison Project?Phase 6) focusing on ice sheets, designed to provide an ensemble of process-based projections of the ice-sheet contribution to sea-level rise over the twenty-first century. However, the behavior of the Antarctic Ice Sheet beyond 2100 remains largely unknown: several instability mechanisms can develop on longer time scales, potentially destabilizing large parts of Antarctica. Projections of Antarctic Ice Sheet evolution until 2300 are presented here, using an ensemble of 16 ice-flow models and forcing from global climate models. Under high-emission scenarios, the Antarctic sea-level contribution is limited to less than 30 cm sea-level equivalent (SLE) by 2100, but increases rapidly thereafter to reach up to 4.4 m SLE by 2300. Simulations including ice-shelf collapse lead to an additional 1.1 m SLE on average by 2300, and can reach 6.9 m SLE. Widespread retreat is observed on that timescale in most West Antarctic basins, leading to a collapse of large sectors of West Antarctica by 2300 in 30%?40% of the ensemble. While the onset date of retreat varies among ice models, the rate of upstream propagation is highly consistent once retreat begins. Calculations of sea-level contribution including water density corrections lead to an additional ?10% sea level and up to 50% for contributions accounting for bedrock uplift in response to ice loading. Overall, these results highlight large sea-level contributions from Antarctica and suggest that the choice of ice sheet model remains the leading source of uncertainty in multi-century projections.
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; klimamodeller